The motivation of rice farmers toward organic rice farming in Sleman Regency - Rahmawati Nur (EDP Sciences, 2021)
This study aims to determine the motivation of rice farmers toward organic rice farming and the factors of their motivation in organic farming. The research was conducted in Sleman Regency as it has applied the principles of organic rice, although not completely. The sample in this study amounted to 91 farmers. This study employed descriptive analysis with scoring technique and motivation model using the ERG theory. The results uncovered that the motivation of rice farmers in Sleman Regency toward organic rice farming, especially on the needs for existence, belonged to the high category with an average score of 3.78, the relatedness needs was included in the high category with an average score of 4.15, and the growth needs was also in the high category with an average score of 3.43. Therefore, the motivation of rice farmers toward organic rice farming in Sleman Regency, particularly in fulfilling primary, interaction, and developing needs, was high.